Digital Transformation of Laundry Businesses Through Digital Marketing: A Case Study of Bagas Laundry Business Group - Oriza Candra; Helmawati Helmawati; Nurzi Sebrina; Syaiful Islami (Jurnal Teknik Elektro Indonesia, 2026)
This article examines digital transformation strategies in the laundry business sector, focusing on the “Bagas Laundry” business group and the implementation of digital marketing-based strategies. The study highlights significant improvements in business growth and operational performance after adopting digital transformation initiatives. Before implementing digital marketing, the market share of “Bagas Laundry” was only 10%, but it increased substantially to 45% by the end of 2022. The study emphasizes the importance of digital marketing strategies, including website and mobile application development, social media marketing, email campaigns, and Search Engine Optimization (SEO), in addressing the limitations of conventional marketing methods. The findings reveal that website traffic increased by 150% within the first six months of implementation, while customer conversion rates improved by 80%. In addition, the adoption of automation systems and digital payment integration enhanced operational efficiency by 30% and reduced order processing time by 40%. Employee training programs related to digital technology adaptation and online marketing skills also produced positive results, leading to a 25% increase in employee productivity. Customer experience improvements became another major focus, resulting in a 90% increase in customer satisfaction and customer retention rates remaining above 80%. Furthermore, the evaluation of Return on Investment (ROI) showed that the business achieved an ROI of 200% in 2022, accompanied by an annual net revenue growth of 120%. Overall, the case study demonstrates that digital transformation significantly improved revenue, market expansion, and customer satisfaction in the laundry business sector.